On the determining and minimizing problems of the duration automata - Vũ Anh, Bùi (Journal of Computer Science and Cybernetics, 2014)
In the previous papers, we have proposed duration automata model and used the model in optimization [3], schedule problems [4] and in problems of the security area [5]. In this paper, we study problem of determining and minimizing the duration automata. Some additional problems are also considered to show how separate and merge durations on the arcs of the automata without changing accepted languages, remove unreachable states (with and without duration meaning). These problems are applied to solve the main problem: determining and minimizing duration automata.